Assessing msme preparedness for compulsory halal certification: A case study of bogor regency, indonesia - Fathan Abdul Fattah Fattah; Betania Kartika Muflih; Mohammad Aizat Jamaludin (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
The Indonesian Government Regulation No. 39 of 2021 mandates halal certification for all food and beverage products, including those produced by MSMEs. This study explores the readiness of MSMEs in Bogor Regency to comply with this regulation and identifies key challenges they face. Using a qualitative case study approach, data were collected through semi-structured interviews with MSME owners, government officials, and halal certification body representatives. The findings reveal low readiness among MSMEs, primarily due to limited knowledge, financial constraints, and infrastructural inadequacies. Although initiatives such as the self-declare scheme and digital platforms have improved accessibility, effectiveness remains hampered by a lack of awareness and technical support. The study highlights the importance of stakeholder collaboration and recommends enhancing training, simplifying procedures, and expanding financial and infrastructural support.